Extracellular Vesicles Secreted by Neospora caninum Are Recognized by Toll-Like Receptor 2 and Modulate Host Cell Innate Immunity Through the MAPK Signaling Pathway - Li, Shan; Gong, Pengtao; Tai, Lixin; Li, Xin; Wang, Xiaocen; Zhao, Chunyan; Zhang, Xu; Yang, Zhengtao; Yang, Ju; Li, Jianhua; Zhang, Xichen (Frontiers in Immunology, 2018)
Neospora caninum is an intracellular parasite that causes significant economic losses in the cattle industry. However, the immune mechanism of the parasite-host interaction is not yet fully understood. Extracellular vesicles (EVs) have emerged as a ubiquitous mechanism by which almost all cells, especially immune and tumor cells, participate in intercellular communications. Although several studies have indicated that the EVs secreted by parasites are a means of exchanging biological molecules that are involved in the host-parasite interplay, little is known to date about N. caninum EVs and their biological activities. Here, we used multiple methods, including electron microscopy, nanoparticle tracking analysis, RT-PCR, immunofluorescence, Western blotting, proteomics and cytokine analyses, to examine the properties of N. caninum EVs. We found that N. caninum produces and secretes EVs that are similar to mammalian exosomes, which generally range from 30 nm to 150 nm in diameter. It was shown that N. caninum EVs could remarkably increase the production of pro-inflammatory IL-12p40, TNF-α, IL-1β, IL-6 and IFN-γ by wild-type (WT) mouse bone marrow-derived macrophages (BMDMs) whereas the secretion of IL-12p40, TNF-α and IFN-γ was very strongly downregulated in TLR2-/- mouse BMDMs. The levels of IL-6 were not affected, but the secretion of IL-10 was upregulated. We found that the phosphorylation levels of P38, ERK and JNK were significantly reduced in the TLR2-/- cells compared with those in WT mouse BMDMs and that treatment with chemical inhibiters of P38, ERK and JNK resulted in upregulation of IL-6, IL-12p40 and IL-10 production. Together, these results demonstrated that N. caninum EVs could be rapidly internalized to deliver proteins to the host cells and modulate the host cell immune responses through the mitogen-activated protein kinase (MAPK) signaling pathway in a TLR2-dependent manner. Our study is the first to reveal a potential role for N. caninum EVs in host communication and immune response, which suggests an important role in parasite-host interactions.